Concept for material supply in fluid manufacturing systems - Manuel Hagg; Robert Schulz (Changing Tides: The New Role of Resilience and Sustainability in Logistics and Supply Chain Management – Innovative Approaches for the Shift to a New Era. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 33, 2022)
Purpose: Through increasing individualization, volatile market demands or shorter product and innovation cycles, existing assembly systems in the automotive industry reach their limits. Different approaches are designed to address the need for adaptable systems. The Fluid Manufacturing System (FLMS), which has been developed within the research campus 'Active Research Environment for the Next generation of Automobiles' (ARENA2036), aims to enable flexible and dynamic material flows. However, material supply in this environment is challenging due to new degrees of freedom or volatile demands. Therefore, the purpose of this paper is to describe a concept for short-term-oriented material supply in FLMS. The concept focuses on checking and ensuring material availability. Methodology: The methodology that is used to derive the concept for material supply is based on a step-by-step procedure allowing a systematic concept development using a problem-solving-oriented approach. The concept procedure includes different steps like concept initiation or selection of a solution. Findings: The result of this paper outlines a concept that supports short-term-oriented material supply in FLMS. More detailed, the concept supports checking and ensuring material availability. Originality: The presented concept contributes to check and ensure material availability during the operation of assembly systems under changing conditions.
urn:nbn:de:gbv:830-882.0200500; hdl:10419/267179; https://econpapers.repec.org/RePEc:zbw:hiclpr:33
Keywords: 650; Advanced Manufacturing; Industry 4.0